QLIF-47. HEALTH RELATED QUALITY OF LIFE AND NEUROLOGICAL DETERIORATION FREE SURVIVAL IN INTELLANCE 2/EORTC TRIAL 1410, A RANDOMIZED PHASE II STUDY ON ABT414 IN RECURRENT EGFR AMPLIFIED GLIOBLASTOMA - Clement, Paul (Neuro Oncol, 2017)
BACKGROUND: Treatment options for recurrent glioblastoma are limited. 45-50% of glioblastoma show EGFR amplification. ABT-414 is a tumor-specific antibody-drug conjugate (ADC) combining an antibody (ABT-806) targeting a unique conformation of EGFR bound to monomethyl auristatin F (MMAF), a microtubule cytotoxin. We investigated ABT-414 in glioblastoma at 1strecurrence, besides Overall Survival (OS) the study endpoints included Quality of Life (QoL) and Neurological Deterioration Free Survival Analysis (NDFS). METHODS: EORTC-1410-BTG (NCT02343406) is a randomized open label phase II study. Eligible were patients with a centrally confirmed EGFR amplified glioblastoma with a first recurrence after combined temozolomide chemo-irradiation, occurring ≥ 3 months after the end of radiotherapy, ≥ 18 years, WHO performance status (PS) 0-2, with adequate organ function, and tissue available for central EGFR and MGMT determination. After stratification for region of the world, WHO status and timing of relapse (< 16 weeks or patients were randomized to either a) treatment with ABT-414 1.0 mg/kg every two weeks intravenously alone, or b) the same treatment in combination with temozolomide 150-200 mg/m2 day1-5 every 4 weeks, or c) either lomustine or temozolomide depending of the time of recurrence in relation to the end of temozolomide treatment in 1stline. QoL was assessed using the EORTC QLQ-C30 questionnaire and the QLQ-BN20 Brain Cancer Module. NDFS was assessed by change in WHO Performance Status; the protocol emphasized the collection of WHO PS beyond progression. Primary endpoint of the study is overall survival (OS); QoL and NDFS are both secondary endpoints. RESULTS: Between Mar 10 2015 and July 22 2016a total of 260 patients were randomized. The per protocol required number of 170 events will be observed in June 2017. The database lock is foreseen for August 2017. At the meeting QOL and NDFS analysis will be presented.